C-Phycocyanin Ameliorates Mitochondrial Fission and Fusion Dynamics in Ischemic Cardiomyocyte Damage - Gao, Jinchao; Zhao, Lidong; Wang, Jinfeng; Zhang, Lihang; Zhou, Dandan; Qu, Jinlong; Wang, Hao; Yin, Ming; Hong, Jiang; Zhao, Wenjuan (Frontiers in Pharmacology, 2019)
Mitochondrial dysfunction is a predominant risk factor in ischemic heart disease, in which the imbalance of mitochondrial fusion and fission deteriorates mitochondrial function and might lead to cardiomyocyte death. C-Phycocyanin (C-pc), an active component from blue green algae, such as Spirulina platensis, has been reported to have anti-apoptosis and anti-oxidation functions. In this study, the effects of C-pc on mitochondrial dynamics of cardiomyocytes was examined using oxygen glucose deprivation/reoxygenation (OGD/R) model in H9c2 cells, an in vitro model to study the ischemia in the heart. Cell viability assay showed that C-pc dose-dependently reduced OGD/R induced cell death. Intracellular reactive oxygen species production induced by OGD/R was decreased in C-pc treated groups in a dose dependent manner as well. H9c2 cells subjected to OGD/R showed excessive mitochondrial fission and diminished mitochondrial fusion. C-pc treatment significantly ameliorated unbalanced mitochondrial dynamics induced by OGD/R and regulated mitochondrial remodeling through inhibiting mitochondrial fission while promoting fusion. The enhanced expressions of mitochondrial fission proteins Dlp1 and Fis1 induced by OGD/R were suppressed by C-pc, while the subdued expressions of mitochondrial fusion proteins Mfn1, Mfn2 and Opa1 induced by OGD/R increased in C-pc treated groups. Triple immunofluorescence staining revealed that C-pc treatment reduced the recruitment of Dlp1 from cytoplasm to mitochondrial membranes. Furthermore, C-pc protected H9c2 cells against OGD/R induced cytochrome c/Apaf1 intrinsic apoptosis and suppressed the phosphorylation of ERK 1/2 and JNK. These results suggest that C-pc protects cardiomyocytes from ischemic damage by affecting mitochondrial fission and fusion dynamics and reducing apoptosis, and thus may be of potential as a prophylactic or therapeutic agent for ischemic heart disease.